Microhabitat Selection for Overwintering: Overwintering Conditions of Three Jumping Spiders (Pellenes tripunctatus, P. nigrociliatus, and Attulus penicillatus) Living in Terrestrial Shells in the Czech Republic - Dziváková, Kristína; Fric, Zdeněk Faltýnek; Hula, Vladimír (Insects, 2022)
Taking the regular overwintering of spider species in land snail shells as a model, we studied environmental conditions affecting the choice of overwintering sites in three jumping spider species: Pellenes tripunctatus, Pellenes nigrociliatus, and Attulus penicillatus. The research was conducted at 11 steppe localities on calcareous bedrock with abundant empty shells (mainly Caucasotachea vindobonensis and Xerolenta obvia). We documented 889 shells and collected 186 of them, of which 113 were inhabited by 146 spider individuals (13 species). Our three focal species made up 81.5% of these. We found different environmental preferences between the sexes in P. tripunctatus and P. nigrociliatus. These females preferred shells with more vegetation nearby. In the case of P. tripunctatus, these were shells with a higher proportion of herbs, whereas P. nigrociliatus selected for a higher proportion of moss. In the immediate vicinity of the shells, environmental conditions did not differ significantly. We found insufficient A. penicillatus to determine any preferences. We also recorded six overwintering P. tripunctatus individuals in a single shell (in environmental conditions preferred by females), consisting of five females and one male, which indicated an unusual social behavior for these spider species.
Keywords: habitat condition; Salticidae; spider behavior; steppe